Environmental Change and Development in Ladakh, Indian Trans-Himalaya - Humbert-Droz, Blaise; Dame, Juliane; Morup, Tashi (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The Trans-Himalayan region of Ladakh has witnessed important changes linked to its geo-strategic importance, the rapid development of means of communication with other parts of India, socio-economic transformation processes and the effects of climate change. The sixteen chapters document these key changes, ranging from melting glaciers and extreme weather events to the exponential increase in infrastructure, tourist and military activities. The book examines the impact these changes are having on the environment and on the socio-economics and identity of Ladakhi communities. The book also attempts to evaluate the likely direction of future changes, identify some of the main environmental challenges faced by Ladakh in the 21st century, and provide perspectives for sustainable development of the high mountain region.
Introduction -- Glaciers of Central Ladakh: Distribution, Changes and Relevance in the Indian Trans-Himalaya -- Floods and Debris Flows in Ladakh: Past History and Future Hazards -- Impact of 2010 Leh Cloudburst: a Psychological Perspective -- Traditional Mathematical Theories of Rainfall Prediction through Lotho as Practised in Ladakh -- The Contribution of Czech Researchers to the Botanical Survey of Ladakh -- The Adaptations of High-Altitude Mushrooms in the Cold Desert of Ladakh -- A Brief Description of Sacred Trees (lhachang) -- Environmental Change in Ladakh's Changthang: a Local, Regional and Global Phenomenon -- Wildlife versus Livestock: Conservation Dilemma of the Pastoralists of Changthang -- Harnessing Traditional Knowledge for Wildlife Conservation in the Ladakh Trans-Himalaya -- Changing Production, Changing Consumption: Food System Transformation in Ladakh -- Eating Habits In and Around Leh Town -- Seeds of Change: A Review of Agricultural Developments in Central Zangskar -- Influences of Tourism, Indian Administration and Army on Community Identity Processes in Padum (Zangskar) -- "We Are Puppets in the Hands of Nature": Road Construction and the Transformation of People-Environment Relationships in Ladakh -- Trade-Off between Continuity and Change in Leh District: an Emergy Evaluation in Time Series: 1999-2011.
Keywords: Sustainability; Climatology; Agriculture; Human geography; Anthropology; Sustainability; Climate Sciences; Agriculture; Human Geography; Anthropology